Shape Programming of Liquid Crystal Elastomers by Two-Stage Wavelength-selective Photo- Polymerisation - Tomé, Daniela Roque (2024)
The stimulus responsiveness properties of liquid crystal elastomers (LCEs) make them prime candidates for actuator applications. Nevertheless, most LCE fabrication methods show critical limitations, such as time-dependency and lack of control due to catalyst-based reactions. This work proposes a novel two-step wavelength-selective photo-polymerisation (TWSP) reaction to synthesise and program thermo-responsive LCEs. By harnessing the power of two photo-initiated reactions, this method provides a higher tailorability control over the LCEs during both crosslinking stages. The independent conversion of ~ 88% acrylates and ~ 26% oxetanes in two separate sequential photo- polymerisation reactions was demonstrated. The LCEs made by TWSP were capable of actuating reversibly over multiple cycles of heating and cooling. It was observed that different alignments can be effectively programmed. Moreover, the usage of different mesogens was viable and led to changes in the LCEs’ properties. For instance, RM82-based stretched films suffered a 35.32% strain variation across a 57 oC window, while C6BAPE-based ones showed a smaller variation of 17.39%, but within a more restricted range of 20 oC. These contraction-based LCEs were found to be capable of lifting a weight 488.81 times heavier than the film itself. A one-pot approach implementation in TWSP showed promise for surface-switching applications but not for making free-standing films due to lower elasticity. Additionally, the TWSP integration with 4D printing was explored with the goal of programming more complex alignments and investigating the possibility of programming alignment in both crosslinking stages. The alignment from printing was found to be sufficient for actuation. However, a second programming in the alignment direction increased the order parameter, resulting in a larger actuation and sharper transition of the LCEs. Conversely, a second programming in the perpendicular direction to the alignment led the film to actuate from flat to a tunnel-like shape due to the competing alignments.